Nutritional Risks in Adolescents After Bariatric Surgery - Xanthakos, Stavra A. (Clin Gastroenterol Hepatol, 2019)
BACKGROUND & AIMS: Little is known about prevalence and risk factors for nutritional deficiencies in adolescents after metabolic bariatric surgery. We performed a 5-year prospective cohort study of these. METHODS: Adolescents who had Roux-en-Y gastric bypass (RYGB, n=161) or vertical sleeve gastrectomy (VSG, n=67) were enrolled at 5 tertiary-care centers from March 2007 through February 2012. The final analysis cohort included 226 participants (161 who had RYGB and 65 who had VSG). We measured serum levels of ferritin; red blood cell folate; vitamins A, D, B1, B12; and parathyroid hormone at baseline and annually for 5 years. General linear mixed models were used to examine changes over time and identify factors associated with nutritional deficiencies. RESULTS: The participants were 75% female and 72% white, with a mean age of 16.5±1.6 years and mean body mass index of 52.7±9.4 kg/m(2) at surgery. Mean body mass index decreased 23% at 5 years, and did not differ significantly between procedures. After RYGB, but not VSG, serum concentrations of vitamin B12 significantly decreased whereas serum levels of transferrin and parathyroid hormone increased. Ferritin levels decreased significantly after both procedures. Hypo-ferritinemia was observed in 2.5% of patients before RYGB and 71% at 5 y after RYGB (P<.0001), and 11 % of patients before VSG and 45% 5 y after VSG (P=.002). No significant changes in serum levels of folate or vitamins A, B1, or D were found between baseline and 5 y after either procedure. By 5 y, 59% of RYGB and 27% of VSG recipients had 2 or more nutritional deficiencies. Risk factors associated with specific deficiencies included surgery type, female sex, black race, supplementation intake, weight regain, and for females, pregnancy. CONCLUSIONS: In a prospective study of adolescents who underwent RYGB or VSG, we observed nutritional deficiencies by 5 y after the procedures—particularly in iron and B12 after RYGB. Ongoing nutrient monitoring and supplementation are recommended for all patients, but surgery type, supplementation intake, sex, and race might affect risk. ClinicalTrials.gov number, NCT00474318.